Hemolytic anemia following intravenous immunoglobulins in children with PIMS-TS: Two case reports - Sedlin, E.; Lau, S.; von Bernuth, H.; Kallinich, T.; Mayer, B. (Frontiers in Pediatrics, 2023)
This is the first case report on two children presenting with an immediate and severe hemolytic anemia following the administration of high-dose intravenous immunoglobulin (IVIG) in the context of Pediatric Inflammatory Multisystem Syndrome temporally associated with SARS-CoV-2 (PIMS-TS). The hemolytic anemia was revealed as a significant drop in hemoglobin (Hb) and an increase in lactate dehydrogenase (LDH) after the second administration of high-dose IVIG was performed. Both patients were found to have blood group AB. One of our patients showed massive pallor, weakness, and inability to walk in association with hemolysis. But in both cases, the anemia itself was self-limiting and transfusion of red blood cells was not required: both patients recovered without persistent impact. Nonetheless, we aim to draw attention to this widely unknown adverse effect of IVIG especially in context of PIMS-TS. We suggest a determination of the patient`s blood group prior to high dose IVIG infusion and a replacement of the second IVIG through high-dose steroids or anti-cytokine therapy. Using IVIG containing lower titers of especially anti-A or anti-B antibodies to avoid isoagglutinin-caused hemolytic anemia is desirable however, the information is not routinely available.